Attitudes towards prisoners, as reported by prison inmates, prison employees and college students - Kjelsberg, Ellen (BioMed Central, 2007)
BACKGROUND: Positive attitudes towards prisoners are important in securing the effectiveness of various correctional rehabilitation programs and the successful reintegration of prisoners after release. We wanted to investigate the attitudes towards prisoners among prison inmates, prison employees and college students. METHODS: The Attitudes Toward Prisoners scale was completed by 298 inmates in 4 Norwegian prisons, 387 employees working in the same prisons, and 183 college students. In addition, all respondents were asked a number of general questions about prisoners, crime and punishment. RESULTS: The study groups differed significantly in their attitudes towards prisoners, as measured by the Attitudes Toward Prisoners scale, with prison inmates holding the most positive attitudes. Prison officers held more negative attitudes than other prison employees. Prison employees working in female-only facilities held more positive attitudes than those working in male-only facilities. Students differed significantly in their attitudes, with those studying business economics holding more negative attitudes than those studying nursing. A number of strong correlations emerged between negative attitudes towards prisoners and more pessimistic and punitive answers on general questions about prisoners, crime and punishment. CONCLUSION: The attitudes towards prisoners differed markedly among the groups investigated. The findings could have important implications, particularly for the preventive work carried out in our prisons. Whether attitudes toward prisoners can be influenced by educational programs and the dispersion of factual information needs to be investigated.